Flexible piezoelectric bionanocomposites for biomedical sensors - Guzmán Sierra, Dayana Lizethe (2018)
In recent decades, there has been increasing interest in the development of new materials in order to achieve the "Internet of Things (IoT)" which provided for the connection of 20 to 30 billion devices to the Internet by 2020. The implementation of the "Internet of Things "requires the development of base technology, which includes transducers, actuators and sensors. Sensors are often used in biomedical applications that require flexibility, biocompatibility and sustainability. In this context, the motivation of this work was the preparation of a bionanocomposite for biocompatible piezoelectric sensors for biomedical applications. Thus, a polysaccharide that have the ability to form films (films), and particles of barium titanate which is ferroelectric and piezoelectric material at room temperature, having no lead in its composition. The BaTiO3 particles were synthesized by hydrothermal method at moderate temperature (200 °C) and in the absence of organic solvents. Several reaction times were studied in order to select the ideal conditions for the particles preparation with the required properties to be incorporated in the chitosan-based films. The structural characterization by X-ray diffraction (XRD) and Raman spectroscopy allowed us to verify that the particles synthesized at 200 °C showed a well-defined tetragonal crystallographic structure after 24 hours of synthesis. The particles showed uniformed cubic morphology and average size of about 306 nm. In general, particle and crystallite sizes increase with reaction time. The films were obtained by the solvent evaporation method, after dispersing the particles in different proportions, in a solution of chitosan. Structural properties (XRD) and morphological (SEM); physical-chemical (mechanical, degree of humidity, solubility in water and contact angle, and Raman); and electrical (dielectric behavior, hysteresis curves and nanoscale piezoelectric response) of the films were characterized. The addition of particles improved the mechanical properties of the chitosan films, making them more resistant, elastic and ductile. These films have also been shown to be more resistant to water, which reveals that there is an interaction between the particles and the chitosan matrix. In relation to the electric behavior of the films, the increase of particles improves the permittivity of the samples five times in relation to the biopolymer material. It was verified a great difficulty of deposition of electrodes in the flexible films that can be justified on the basis of the characteristics of the samples and / or the inadequacy of the experimental conditions of deposition of the electrodes in the sample. It was not possible to measure the piezoelectric response at the macroscopic scale nor to polarize an area of the bionanocomposite sample. Thus, the piezoelectric response at the nanometric scale was studied by atomic microscopy of piezoelectric response. It was found that nanocomposite films with the highest concentration of nanoparticles clearly showed piezoelectric domains, but it is not possible to obtain an acceptable hysteresis curve and to polarize a small area of the nanocomposite. These observations, together with the analysis by surface potential microscopy of the control film (chitosan only) that indicates the presence of charges in the pure polymer, lead to the conclusion of an electret type behavior, being necessary a strategy to eliminate (or reduce) the matrix's contribution. Despite the difficulties encountered due to degree of innovation of the work, the bionanocomposites developed based on chitosan and barium titanate are promising to be used in biomedical devices (drug release pads, etc.) since they have high mechanical resistance, elasticity, and ductility, as well as have higher resistance to conditions with high degree of humidity. In addition, they are biocompatible and partially biodegradable, being an excellent alternative to synthetic polymers